Quantmare, August 2007 - Murray, Eoin (Henry Stewart Talks, 2010)
Quantitative investing, Equity market neutral, Quantmare, August 2007, Factor models, Credit crisis, Volatility, Liquidity, Overcrowded trades, Leverage, Correlation, Value investing, Risk models, Factor rotation, Regime switching, Correlations and copulas, Systematic strategies
Archived at 2022/04/04